Experiencias de los proyectos de produccion de semilla para los pequenos productores en Colombia y su relacion con la investigacion en fincas - Arias R., J.H. (International Center for Tropical Agriculture, 1987)
The successful program for certified seed production of beans and maize for the farmers of eastern Antioquia is described. The Instituto Colombiano Agropecuario produces the basic seed that is then sold to farmers previously selected as seed multipliers. By an agreement with the Caja Agraria, these farmers produce certified quality seed that is sold to the Caja Agraria which takes care of the benefit, distribution, and sale of the certified seed. In this region, it is very important that the grain produced have similar color and size to those of regional var. Cargamanto. This program is supplemented by a technology transfer plan directed to farmers and users of certified seed. (CIAT)